1996
DOI: 10.1093/amt/21.1.406a
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Insecticides for Control of Tarnished Plant Bug in Mississippi, II, 1995

Abstract: Insecticides were evaluated at Mississippi State University in a randomized complete block design with 4 replications. Insecticides were applied on 31 May in a spray chamber equipped with a single Spraying Systems TX3 hollow cone nozzle and calibrated for 5 gpa at a pressure of 28 psi and a speed of 3 mph. Carrier of the insecticides was water, with an initial pH of 8.0. Plant bugs were collected the morning of application by sweeping wild flowers with a 15 inch diameter sweep net. Leaves were collected in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This paper continues a history of the reporting of assay responses of tarnished plant bug to the major classes of insecticide used in the Delta. There is a wealth of previous information on tarnished plant bug response to insecticides in this area, including early work [ 43 , 44 ], numerous papers from the Snodgrass laboratory [ 7 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 22 , 45 ], studies in Arkansas [ 29 , 33 ], studies in Louisiana [ 46 , 47 ], a summary of small-plot field experiments in Mississippi [ 2 ], and a number of efforts to understand tarnished plant bug resistance mechanisms [ 1 , 23 , 25 , 26 , 27 , 28 ]. Understanding the changes in susceptibility over time are important, but understanding how these changes evolve and how management practices can be refined with this information is particularly relevant to managing tarnished plant bugs in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This paper continues a history of the reporting of assay responses of tarnished plant bug to the major classes of insecticide used in the Delta. There is a wealth of previous information on tarnished plant bug response to insecticides in this area, including early work [ 43 , 44 ], numerous papers from the Snodgrass laboratory [ 7 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 22 , 45 ], studies in Arkansas [ 29 , 33 ], studies in Louisiana [ 46 , 47 ], a summary of small-plot field experiments in Mississippi [ 2 ], and a number of efforts to understand tarnished plant bug resistance mechanisms [ 1 , 23 , 25 , 26 , 27 , 28 ]. Understanding the changes in susceptibility over time are important, but understanding how these changes evolve and how management practices can be refined with this information is particularly relevant to managing tarnished plant bugs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Recommended application rates of acephate were increased from 0.23–0.33 lb ai/acre to 0.5–1.0 lb ai/acre during this time period ( Table 10 ), indicating a growing concern for the level of field control being achieved. Reed et al [ 2 ] summarized results of replicated field experiments conducted to measure tarnished plant bug control in cotton with organophosphate insecticides, and reported that the average control measured from 1982 to 1997 was 57%. If this level of field control compares to the previous assay data of Snodgrass et al [ 21 ], and field control is even loosely related to changes in assay response, acephate applications alone do not adequately control tarnished plant bugs in the field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations